2021
DOI: 10.1002/ejoc.202100953
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Cross‐Dehydrogenative Couplings of 8‐Aminoquinoline Amides at C5 Position with Acetonitrile, Ethers or Acetone

Abstract: A novel and efficient method for highly regioselective cyanomethylation of 8-aminoquinoline amides at C5 position was developed. Such reactions proceed under transition metalfree and base-free conditions. This protocol features simple operation, high efficiency, good functional group tolerance and broad substrate scope. Moreover, the etherification or acetonation products were also obtained when acetonitrile was replaced by ethers or acetone, and a radical process was involved in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the last few years, metal-free catalyzed direct cyanomethylation of C-H bonds, including C(sp2)-H bonds [35,36] and C(sp3)-H bonds [37], has emerged as a powerful tool in organic synthesis, which has the advantages of atom economy. In 2018, Zhang et al [35] reported the synthesis of cyanomethylcoumarin via a cross-dehydrogenation coupling reaction between coumarin 16 and acetonitrile (Scheme 5).…”
Section: Transition Metal-free Cyanomethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, metal-free catalyzed direct cyanomethylation of C-H bonds, including C(sp2)-H bonds [35,36] and C(sp3)-H bonds [37], has emerged as a powerful tool in organic synthesis, which has the advantages of atom economy. In 2018, Zhang et al [35] reported the synthesis of cyanomethylcoumarin via a cross-dehydrogenation coupling reaction between coumarin 16 and acetonitrile (Scheme 5).…”
Section: Transition Metal-free Cyanomethylationmentioning
confidence: 99%
“…Subsequently, the cyanomethyl radical is generated by the hydrogen abstraction of acetonitrile by the tert- Cyanomethylation can also occur in the absence of a base. In 2021, Liu et al [36] developed a method for the cyanomethylation of 8-aminoquinoline amides 20 (Scheme 6). This method uses only TBPB as an oxidant in the absence of metal catalysts and bases.…”
Section: Transition Metal-free Cyanomethylationmentioning
confidence: 99%
“…On the other hand, direct radical coupling α-C–H of ethers has emerged as one of the most versatile tools to construct a wide variety of α-substituted ether derivatives, and many meaningful accomplishments have been made in this field . However, most of these approaches required transition metals as catalysts and stoichiometric explosive peroxides as oxidants at high temperatures . Such reaction conditions may result in metal residue and safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Some protocols have been disclosed to recognize direct coupling between acetonitrile and aromatic hydrocarbons such as furans, 11 thiophenes, 11 2-arylimidazo-[1,2-a] pyridine, 12 indoles, 13 and aminoquinolines. 14 In previous reports, the dehydrogenation-coupled cyanomethylations were mainly concentrated in the electron-rich position of some particular aromatic rings, which might be because the cyano C-centered radical is electrophilic, 11 and this transformation is rarely reported in benzenes 15 and electrondeficient pyridine rings. Herein, we report a novel and efficient FeCl 2 /DTBP-promoted C(sp 3 )−C(sp 2 ) coupling between acetonitrile and arylamines, where the amino group is necessary for this transformation and directs the cyanomethy- lation reaction to its ortho position.…”
mentioning
confidence: 99%
“…In recent years, the radical-mediated cross-dehydrogenative coupling (CDC) reaction has become a useful tool for realizing aromatic hydrocarboylation because these reactions have the advantages of atom economy, high efficiency, and environmental friendliness. Some protocols have been disclosed to recognize direct coupling between acetonitrile and aromatic hydrocarbons such as furans, thiophenes, 2-arylimidazo­[1,2- a ] pyridine, indoles, and aminoquinolines . In previous reports, the dehydrogenation-coupled cyanomethylations were mainly concentrated in the electron-rich position of some particular aromatic rings, which might be because the cyano C-centered radical is electrophilic, and this transformation is rarely reported in benzenes and electron-deficient pyridine rings.…”
mentioning
confidence: 99%